On the genus Elegia Ragonot, 1887 (Pyralidae: Phycitinae: Phycitini) from Iran with description of Elegia kharazii sp. nov. - Alipanah, Helen; Slamka, František (Zootaxa, 2021)
Elegia species deposited in the Hayk Mirzayans Insect Museum (HMIM) were examined and three species were identified. Elegia kharazii sp. nov. is described based on a single male and two females collected in Gilan and Golestan Provinces, Iran and compared with the externally similar European species E. similella (Zincken, 1818). Elegia saecula Kemal, Kýzýldað & Koçak, 2020 (syn. nov.) is considered as a junior synonym of Elegia iozona (Meyrick, 1937). Elegia atrifasciella Ragonot, 1887, collected in the north-west Iran (East Azarbaijan Province), is a new species for the fauna of Iran.